PENGARUH LATIHAN INTERVAL TRAINING TERHADAP PENINGKATAN DAYA TAHAN ATLET SEPAK BOLA USIA 13-18 TAHUN CLUB GIK TAHUN 2025 - Jeskiel Tarigani; Julius Boy Nesra Basgimata Barus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of interval training on increasing physical endurance (VO₂ Max) of football athletes aged 13-18 years at Club GIK (Generasi Inspiratif Karo). The background of the research is the problem of athletes who often experience fatigue and decreased performance towards the end of the match due to a training program that has not been focused on endurance. This research uses an experimental method with One Group Pretest-Posttest Design. The sample consisted of 15 athletes selected using total sampling technique. The treatment given was interval training in the form of repeated 20-meter sprints (HIIT) carried out for 16 meetings. The instrument used was the Beep Test or Multistage Fitness Test. Data analysis used normality test, homogeneity test, and Paired Sample t-Test. The results showed that the average VO₂ Max value increased from 44.55 ml/kg/min in the pretest to 50.35 ml/kg/min in the posttest. Statistical test obtained a significance value of 0.000 (< 0.05), so Ha is accepted. It was concluded that interval training has a significant effect on increasing the physical endurance of Club GIK athletes. This method is recommended for coaches to improve the physical fitness of young players.